The riddle of the hidden treasure - Blyton, Enid; Baverstock, Gillian (Award Publications Worksop, England, 2014)
The Riddle of the Hidden Treasure by Enid Blyton is an exciting mystery novel where a group of children embarks on an adventure to find a long-lost treasure. When they discover an ancient map and clues leading to the hidden fortune, the children must solve puzzles and riddles to uncover its location. Along the way, they face challenges, including competing treasure hunters and tricky obstacles. Using their wit, teamwork, and courage, the group unravels the mystery of the treasure, learning valuable lessons about friendship and determination in the process.